Akuntabilitas dan Transparansi Pengelolaan Alokasi Dana Desa - Intan Nuraeni; Tjokorda Gde Budi Kusuma (Jurnal Ilmiah Akuntansi Kesatuan, 2021)
The purpose of this research is to find out how accountability and transparency in the management of village fund allocation (ADD) Case Study in Sukamahi Village, Megamendung Subdistrict, Bogor Regency in 2020. This study uses qualitative with a descriptive approach or more commonly called qualitative descriptive. The results showed that the accountability of ADD management in Sukamahi Village has been good, both technically and administratively, as well as the transparency of ADD management in Sukamahi Village also runs transparently this can be seen from the existence of easily accessible information and the existence of good communication between village devices and the community so that add management is considered transparent. Although the management of ADD in Sukamahi Village can be categorized well but in the management of ADD itself there are still obstacles that are rules governing ADD always change both in every year and in the same year that makes the village devices, especially those directly involved in the management of ADD must continue to learn and understand every new regulation and always change every activity that will be done in accordance with the regulations so that accountability and transparency management of ADD can be maintained. Keywords: Accountability, Transparency, Management of Village Fund.